Assessing the Causal Role of Selenium in Amyotrophic Lateral Sclerosis: A Mendelian Randomization Study - He, Di; Cui, Liying (Frontiers in Genetics, 2021)
Objectives: The relation between selenium overexposure and increased risk of amyotrophic lateral sclerosis (ALS) has been subject to considerable interest. Epidemiologic studies have reported suggestive associations between selenium and ALS, although the causal inference between selenium and ALS remains to be established. Methods: We conducted a two-sample Mendelian randomization (MR) analysis to analyze the causal role of selenium on ALS risk. Variants associated with selenium levels were obtained from the GWAS meta-analysis of circulating selenium levels (n = 5,477) and toenail selenium levels (n = 4,162) in the European population. Outcome data were from the largest ALS GWAS dataset with 20,806 ALS cases and 59,804 controls in the European population. Inverse variance weighted (IVW) method was used as the main analysis, with an array of sensitivity analyses performed to detect potential violations of MR assumptions. Results: Inverse variance weighted (IVW) analysis indicated no evidence of a causal role for selenium levels in ALS development (odds ratio [OR] = 1.02, 95% confidence interval [CI] = 0.96–1.08). Similar results were observed for sensitivity analyses (OR = 1.00, 95% CI 0.95–1.07 for weighted median; OR = 1.07, 95% CI = 0.87–1.32 for MR-Egger), with no pleiotropy detected. Conclusions: Although selenium was found associated with ALS according to earlier epidemiologic studies, current evidence based on population of European ancestry does not support the causal effect of selenium on ALS risk.